المبادئ الاساسية لمشروع محمد اركون الفكري في قراءته للتراث الاسلامي - ابراهيم حسين باقر (lark, 2018)
The research attempts to investigate the critical foundations of the Mohammed Arcon intellectual project against the various writings of discourse which deal with Islamic religion both in Islamic space and in Western space represented in the writings of orientalists, illustrating the systematic and structural flaws involved in these discourse. On the other hand, the research reviews the foundations of the Arcon methodology, which draws from various human studies, the most modern and scientific concepts, from anthropological, psychological, social, psychological, historical and philosophical studies. The proposed approach of Arcon is within the framework of its extensive and multi- It is a concept against the (classic Islamism), specifically the Orientalism .